(untitled) (Economic studies journal, 2021)
Abstract The subject of this research is one of the important topics that raise many aspects related to the challenges facing state building, depleting their financial resources, and threatening their stability, and the phenomenon of money laundering or laundering is one of the forms of economic crimes developed at the present time, which is largely related to illegal activities usually Fugitive funds are outside the limits of the validity of laws against financial corruption, and then returned again in a legitimate manner recognized by the same laws that criminalized them in these countries, where the dirty money derived through crime is cleaned without disclosing Its illegal source is through its introduction into legal banking channels to give it legitimacy to it, and then use it in financial operations and enter it in legitimate areas of investment, and thus it is integrated into those projects and it is not possible to refer to its origin The research aims to shed light on the phenomenon of money laundering or laundering as an international economic crime that transcends the international laws and norms that criminalize it. and calls for greater efforts to be made to limit and confront it .